Contesting science by appealing to its norms: readers discuss climate science in the Daily Mail - Jaspal, Rusi; Nerlich, Brigitte; Koteyko, Nelya (Sage, 2013)
This study examines the rhetorical aspects of social contestation of climate change in reader comments published in the Daily Mail, subsequent to climategate. The following themes are reported: (1) denigration of climate scientists to contest hegemonic representations, (2) delegitimization of pro–climate change individuals by disassociation from science, and (3) outright denial: rejecting hegemonic social representations of climate change. The study outlines the discursive strategies employed in order to construct social representations of climate change, to contest alternative representations, and to convince others of the validity of these representations.It examines how social representations of science are formed, maintained,and disseminated.